Disclosure of Provisions in Financial Statements of Public Companies - Klimczak, Katarzyna (Studia Oeconomica Posnaniensia, 2016)
The article presents the results of the research devoted to financial reporting of provisions by public companies listed on Warsaw Stock Exchange. The aim of the research was the analysis of the scope of disclosures in consolidated annual reports. The analysis included the presentation of provisions in a statement of financial position and in notes to financial statement.